Assessment of water quality and health risks for toxic trace elements in urban Phewa and remote Gosainkunda lakes, Nepal. Issue 5 (4th July 2017) - Rupakheti, Dipesh; Tripathee, Lekhendra; Kang, Shichang; Sharma, Chhatra Mani; Paudyal, Rukumesh; Sillanpää, Mika
ABSTRACT: The concentration of 13 metals (Al, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, As, Cd, Pb, and Hg) and their associated health risk assessment was performed for two Himalayan lakes, urban Phewa and remote Gosainkunda, from Nepal. Water Quality Index (WQI), Metal Index (MI), Hazard Quotient (HQ), Hazard Index, and Cancer Risk were calculated in order to evaluate the water quality of these lakes. Correlation analysis revealed that Mn and Fe were derived from natural geological weathering processes and Pb, V, Cr, Co, Ni, Cu, Zn, and Cd might have originated from anthropogenic sources. The results revealed that WQI of the remote lake fell into excellent water quality and urban lake fell into poor water quality, which is also supported by the MI calculation. Moreover, the HQ of Mn in urban lake showed values greater than unity suggesting its health risk to the local inhabitants. The cancer index values indicated "high" risk due to Cr, whereas Cd possesses "very low" cancer risk on local population residing nearby areas. This study provides the useful database and suggests for the regular assessment and policy formulation for safeguarding the natural water bodies in the region.